Description of a new species of Cnemaspis (Squamata: Gekkonidae) from Knuckles Range of Sri Lanka - Batuwita, Sudesh; Udugampala, Sampath (Zootaxa, 2017)
A new species of Cnemaspis Strauch is described from Knuckles Range of Sri Lanka. This new species had been previously confused with Cnemaspis podihuna Deraniyagala. Cnemaspis kandambyi sp. nov. closely resembles C. podihuna and C. molligodai Wickramasinghe & Munindradasa. Cnemaspis kandambyi sp. nov. differs from C. podihuna by having 7–8 (versus 3–6) unpored scales in each side of the precloacal-femoral pores row, lacking (versus having) an internasal scale, body (axilla to groin) relatively long 47.7–48.3 (versus 38.1–38.7)% of SVL and dorsum dark brown (versus bright yellow). Cnemaspis kandambyi sp. nov. also distinguished from C. molligodai by having 4 (versus 5) precloacal pores, 5–6 (versus 7–9) femoral pores on each side, precloacal pores not in an inverted V-shaped arrangement (versus in inverted V-shaped arrangement), lacking (versus having) a distinct black marking on nape and a black lateral stripe begins behind eye extends laterally beyond the origin of forearm (versus not extending beyond the origin of forearm). Additionally, Cnemaspis kandambyi sp. nov. and C. molligodai show discrete distribution: former restricted to Knuckles Range and the latter confined to Lowland wet zone of Sri Lanka. We confirm that, no type material of Cnemaspis podihuna survive in the current collection of the National Museum of Sri Lanka.